Anthropometric, Metabolic and Molecular Determinants of Human Epidermal Growth Factor Receptor 2 Expression in Luminal B Breast Cancer. Issue 8 (August 2015) - Vici, Patrizia; Crispo, Anna; Giordano, Antonio; Lauro, Luigi Di; Sperati, Francesca; Terrenato, Irene; Pizzuti, Laura; Sergi, Domenico; Mottolese, Marcella; Botti, Claudio; Grimaldi, Maria; Capasso, Immacolata; et al.
<x xml:space="preserve">Abstract</x> Genomic and trascriptomic profiling has recently contributed details to the characterization of luminal B breast cancer. We explored the contribution of anthropometric, metabolic, and molecular determinants to the multifaceted heterogeneity of this breast cancer subtype, with a specific focus on the association between body mass index (BMI), pre‐treatment fasting glucose, hormone receptors, and expression of human epidermal growth factor receptor 2 (HER2). Extensively annotated specimens were obtained from 154 women with luminal B breast cancer diagnosed at two Italian comprehensive cancer centres. Participants' characteristics were descriptively analyzed overall and by HER2 status (positive vs. negative). BMI (<25 vs ≥25), pre‐treatment fasting glucose (<median value of 94 mg/dl vs. ≥94) and percentage of hormone receptors were tested for association with HER2 expression in regression models. In univariate models, BMI, fasting glucose and, at a lesser extent, percentage of estrogen receptors (ER) were significantly and inversely associated with HER2 expression (OR: 0.32, 95% CI: 0.16–0.66; 0.43, 0.23–0.82; 0.96, 0.94–0.97, respectively). The multivariate models confirmed the protective role of BMI and ER on HER2 expression, with luminal B HER2 positive patients being significantly less frequent among women within the highest category of BMI and percentage expression of ER compared with their counterparts (OR: 0.22, 95% CI: 0.09–0.53; 0.95, 0.93–0.97). In conclusions, BMI and percentage of ER representation are inversely associated with HER2 expression in luminal B breast cancers. Upon confirmatory findings, this might help identify patient subgroups who may best benefit from the use of interventions targeting insulin resistance in well depicted breast cancer scenarios. J. Cell. Physiol. 230: 1708–1712, 2015. © 2014 Wiley Periodicals, Inc.